A prospective study on the efficacy of Pipelle biopsy to diagnose endometrial pathology in patients with abnormal uterine bleeding - Mathew, Sunitha Mary; Thomas, Pramod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abnormal uterine bleeding is one of the most common problem encountered in gynaecology clinics. Assessment of endometrial pathology is recommended to rule out malignancy and premalignant conditions. Endometrial sampling can be done by Pipelle biopsy in outpatient units as well as by conventional dilatation and curettage in an operation theatre setup. Our study aims to find out the efficacy of office endometrial biopsy in terms of its sample adequacy, diagnostic accuracy and patient acceptability. Methods: 120 women presenting with abnormal uterine bleeding were included. A detailed history along with clinical examination findings are entered in the proforma. Ultrasound scan was done for all of them to identify pelvic pathology and endometrial thickness. Endometrial sampling was then done with Pipelle without anaesthesia. Histopathology reports are collected and sample adequacy and pattern were analysed. Patients are subsequently followed up for a period up to one year. Those who underwent hysterectomy are analysed for the endometrial pathology in hysterectomy specimen which is used as gold standard and compared with Pipelle endometrial sampling histopathology. Results: Sample adequacy for Pipelle biopsy was found to be 96%. Diagnostic accuracy for atypical hyperplasia and adenocarcinoma is 92.5% and 94% respectively. In hysterectomy specimens, carcinoma endometrium coexisted with atypical hyperplasia in 40% of cases with atypical hyperplasia in pipelle biopsy report. Conclusions: Thus, Pipelle endometrial biopsy is a cost-effective method for endometrial sampling except for focal lesions.